If the sum of m terms of an A.P. is the same as the sum of its n terms, show that the sum of its (m + n) terms is zero.
Answer
Verified
510.6k+ views
Hint: Let us assume a variable $a$ which represents the first term of the arithmetic progression, a variable $d$ which represents the common difference of the arithmetic progression. The sum of r terms of this arithmetic progression is given by the formula ${{S}_{r}}=\dfrac{r}{2}\left( 2a+\left( r-1 \right)d \right)$. Using this formula, we can solve this question.
Complete step-by-step answer:
Before proceeding with the question, we must know the formula that will be required to solve this question.
In arithmetic progression, if we have an arithmetic progression with its first term equal to a and its common difference equal to d, then, the sum of its first r terms is given by the formula,
${{S}_{r}}=\dfrac{r}{2}\left( 2a+\left( r-1 \right)d \right)$ . . . . . . . . . . (1)
In this question, it is given that the sum of m terms of an A.P. is the same as the sum of its n terms and we have to show that the sum of its (m + n) terms is zero.
Let us assume an A.P. with its first term as a and common difference as d. Using formula (1), the sum of m terms of this A.P. is equal to,
${{S}_{m}}=\dfrac{m}{2}\left( 2a+\left( m-1 \right)d \right)$ . . . . . . . . . . . . (2)
Using formula (1), the sum of n terms of this A.P. is equal to,
${{S}_{n}}=\dfrac{n}{2}\left( 2a+\left( n-1 \right)d \right)$ . . . . . . . . . . . . (3)
Since in the question, it is given ${{S}_{m}}={{S}_{n}}$, from equation (2) and (3), we get,
\[\begin{align}
& \dfrac{m}{2}\left( 2a+\left( m-1 \right)d \right)=\dfrac{n}{2}\left( 2a+\left( n-1 \right)d \right) \\
& \Rightarrow m\left( 2a+\left( m-1 \right)d \right)=n\left( 2a+\left( n-1 \right)d \right) \\
& \Rightarrow 2am+{{m}^{2}}d-md=2an+{{n}^{2}}d-nd \\
& \Rightarrow 2am-2an+{{m}^{2}}d-{{n}^{2}}d-md+nd=0 \\
& \Rightarrow 2a\left( m-n \right)+\left( {{m}^{2}}-{{n}^{2}} \right)d-d\left( m-n \right)=0 \\
\end{align}\]
There is a formula ${{m}^{2}}-{{n}^{2}}=\left( m-n \right)\left( m+n \right)$. Substituting this formula in the above equation, we get,
\[\begin{align}
& 2a\left( m-n \right)+\left( m-n \right)\left( m+n \right)d-d\left( m-n \right)=0 \\
& \Rightarrow \left( m-n \right)\left( 2a+\left( m+n \right)d-d \right)=0 \\
& \Rightarrow \left( m-n \right)\left( 2a+\left( m+n-1 \right)d \right)=0 \\
& \Rightarrow \left( 2a+\left( m+n-1 \right)d \right)=0..................\left( 4 \right) \\
\end{align}\]
Using formula (1), the sum of (m + n) terms is equal to,
${{S}_{m+n}}=\dfrac{\left( m+n \right)}{2}\left( 2a+\left( m+n-1 \right)d \right)$
From equation (4), substituting \[\left( 2a+\left( m+n-1 \right)d \right)=0\] in the above equation, we get,
$\begin{align}
& {{S}_{m+n}}=\dfrac{\left( m+n \right)}{2}\left( 0 \right) \\
& \Rightarrow {{S}_{m+n}}=0 \\
\end{align}$
Hence, we have proved that the sum of (m + n) terms of this A.P. is zero.
Note: In the equation (4), we can cancel the factor (m - n) only when $m-n\ne 0$. Since this question, m and n are written separately, we can assume that m and n are different and hence, we can say $m-n\ne 0$.
Complete step-by-step answer:
Before proceeding with the question, we must know the formula that will be required to solve this question.
In arithmetic progression, if we have an arithmetic progression with its first term equal to a and its common difference equal to d, then, the sum of its first r terms is given by the formula,
${{S}_{r}}=\dfrac{r}{2}\left( 2a+\left( r-1 \right)d \right)$ . . . . . . . . . . (1)
In this question, it is given that the sum of m terms of an A.P. is the same as the sum of its n terms and we have to show that the sum of its (m + n) terms is zero.
Let us assume an A.P. with its first term as a and common difference as d. Using formula (1), the sum of m terms of this A.P. is equal to,
${{S}_{m}}=\dfrac{m}{2}\left( 2a+\left( m-1 \right)d \right)$ . . . . . . . . . . . . (2)
Using formula (1), the sum of n terms of this A.P. is equal to,
${{S}_{n}}=\dfrac{n}{2}\left( 2a+\left( n-1 \right)d \right)$ . . . . . . . . . . . . (3)
Since in the question, it is given ${{S}_{m}}={{S}_{n}}$, from equation (2) and (3), we get,
\[\begin{align}
& \dfrac{m}{2}\left( 2a+\left( m-1 \right)d \right)=\dfrac{n}{2}\left( 2a+\left( n-1 \right)d \right) \\
& \Rightarrow m\left( 2a+\left( m-1 \right)d \right)=n\left( 2a+\left( n-1 \right)d \right) \\
& \Rightarrow 2am+{{m}^{2}}d-md=2an+{{n}^{2}}d-nd \\
& \Rightarrow 2am-2an+{{m}^{2}}d-{{n}^{2}}d-md+nd=0 \\
& \Rightarrow 2a\left( m-n \right)+\left( {{m}^{2}}-{{n}^{2}} \right)d-d\left( m-n \right)=0 \\
\end{align}\]
There is a formula ${{m}^{2}}-{{n}^{2}}=\left( m-n \right)\left( m+n \right)$. Substituting this formula in the above equation, we get,
\[\begin{align}
& 2a\left( m-n \right)+\left( m-n \right)\left( m+n \right)d-d\left( m-n \right)=0 \\
& \Rightarrow \left( m-n \right)\left( 2a+\left( m+n \right)d-d \right)=0 \\
& \Rightarrow \left( m-n \right)\left( 2a+\left( m+n-1 \right)d \right)=0 \\
& \Rightarrow \left( 2a+\left( m+n-1 \right)d \right)=0..................\left( 4 \right) \\
\end{align}\]
Using formula (1), the sum of (m + n) terms is equal to,
${{S}_{m+n}}=\dfrac{\left( m+n \right)}{2}\left( 2a+\left( m+n-1 \right)d \right)$
From equation (4), substituting \[\left( 2a+\left( m+n-1 \right)d \right)=0\] in the above equation, we get,
$\begin{align}
& {{S}_{m+n}}=\dfrac{\left( m+n \right)}{2}\left( 0 \right) \\
& \Rightarrow {{S}_{m+n}}=0 \\
\end{align}$
Hence, we have proved that the sum of (m + n) terms of this A.P. is zero.
Note: In the equation (4), we can cancel the factor (m - n) only when $m-n\ne 0$. Since this question, m and n are written separately, we can assume that m and n are different and hence, we can say $m-n\ne 0$.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
Define least count of vernier callipers How do you class 11 physics CBSE
The combining capacity of an element is known as i class 11 chemistry CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
Find the image of the point 38 about the line x+3y class 11 maths CBSE
Can anyone list 10 advantages and disadvantages of friction
Distinguish between Mitosis and Meiosis class 11 biology CBSE